Trust and the value of CSR during the global financial crisis. (5th November 2020) - Berkman, Henk; Li, Michelle; Lu, Helen
Abstract: Lins, Servaes and Tamayo (2017) (LST) show that during the Global Financial Crisis (GFC) US firms with high corporate social responsibility (CSR) ratings increased in value relative to firms with low CSR ratings. Our study raises questions about the internal and external validity of the inferences in LST. For a similar sample of US stocks, we find no evidence that high CSR firms outperformed low CSR firms during the GFC when we use a calendar‐time portfolio analysis that controls for industry, or uses value‐weighted portfolios. For a sample of Japanese stocks, we also fail to confirm the results reported in LST.